Public Humanities and the Spanish Civil War Connected and Contested Histories (Palgrave Studies in Cultural Heritage and Conflict, 2018)
This interdisciplinary collection of essays examines contemporary public history's engagement with the Spanish Civil War. The chapters discuss the history and mission of the main institutional archives of the war, contemporary and forensic archeology of the war, burial sites, the affordances of digital culture in the sphere of war memory, the teaching of the war in Spanish school curricula, and the place of war memory within human rights initiatives. Adopting a strongly comparative focus, the authors argue for greater public visibility and more nuanced discussion of the Civil War's legacy, positing a virtual museum as one means to foster dialogue.